47.0k views
2 votes
5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 HELP MEE

User Irosenb
by
6.1k points

2 Answers

5 votes
Hey there!

To start, first simplify your expression by distributing your values to the equation inside the parenthesis:
5(-3x - 2) - (x - 3) = -4(4x + 5) + 13
(5*-3x)+(5*-2)-x-3=(-4+4x)+(-4*5)+13
-15x-10-x-3=-16x-20+13

Now, combine your like terms, or terms that are raised to the same power and have the same variables that are also raised to the same power:
-15x-10-x-3=-16x-20+13
(-15x-x)+(-10-3)=-16x+(-20+13)
-16x-7=-16x-7

Because your equation is set equal to itself, your answer would be all real solutions as any real number can be plugged into the variable and have a valid answer.

Hope this helps and have a wonderful day! :)
User Mohabbati
by
6.5k points
4 votes
first we should simplify!

to do this you need to use the distributive property

-15x - 10 - x + 3 = -16x -20 + 13

now add like terms

-16x - 7 = -16x -7

this is true

S = {Reals}
^
|
|
S means set
{reals} means all real numbers

i hope this helps !!
User Andino
by
6.4k points